Sustainable construction : - Kibert, Charles J. (John Wiley & Sons, 2016)
Sustainable construction has gone mainstream, and will one day be the industry norm. This book provides a comprehensive reference to all aspects of a project to show you how green building concepts and principles apply throughout the design and construction process. Get up to date on the latest green building codes and standards. Learn about the newest technology in green building materials. Adopt the best practices in procurement and delivery systems. Apply sustainability concepts to all aspects of construction and design. Green buildings operate at a very high level of efficiency, which is made possible only by careful consideration every step of the way. Appropriate land use, landscaping, construction materials, siting, water use, and more all play a role in a structure's ultimate carbon footprint. Sustainable Construction provides clear guidance for all aspects of green building, including the most recent advances and the latest technology.